FENOMENA PENGAWASAN PEMILIHAN KEPALA DAERAH DI KALIMANTAN TENGAH MASA PANDEMI COVID-19 - Sandi, Jhon Retei Alfri; ., Suprayitno (Jurnal Politik Pemerintahan Dharma Praja, 2020)
This study is to provide an overview related to the supervision of local elections in Central Kalimantan during the co-19 pandemic. The method used is the study of literature studies. The author examines the phenomena related to election supervision in Central Kalimantan based on existing phenomena and from various literary sources to support the author in presenting the results of the study in question. One indicator of the implementation of post-conflict local elections that is transparent, professional and responsible is related to the extent to which supervision is carried out properly despite the current non-natural disaster covid-19. Related to this, several things were delivered, namely: 1.) The Need for Regional Executive-Legislative Relations in Good COVID-19 Budget Policy, 2). Bawaslu As a supervisor must exist and continue to innovate in supervision during the pandemic, 3). The Covid-19 disaster should not be used as a campaign event.